Interaction Between Chinese Medicine and Warfarin: Clinical and Research Update - Zhuang, Wei; Liu, Shaoli; Zhao, Xusheng; Sun, Nan; He, Tao; Wang, Yali; Jia, Beibei; Lin, Xiaolan; Chu, Yanqi; Xi, Shengyan (Frontiers in Pharmacology, 2021)
Background: Warfarin is a commonly used oral anticoagulant. It has a narrow therapeutic window and wide variation in individualized dosing, and is used clinically for the treatment of thromboembolic diseases. Due to the widespread use of traditional Chinese medicine (TCM) in China and the complex composition and diverse mechanisms of action of TCM, the combination of TCM and warfarin in patients has led to fluctuations in the international normalized ratio of warfarin or bleeding. To ensure rational clinical use, we summarize the TCMs with which warfarin interacts and the possible mechanisms, with a view to providing a clinical reference. Aim of the study: To summarize the mechanisms by which Chinese herbal medicines affect the enhancement or weakening of the anticoagulant effect of warfarin, to provide theoretical references for clinicians and pharmacists to use warfarin safely and rationally, and to avoid the adverse effects associated with the combination of Chinese herbal medicines and warfarin. Methods: A computerized literature search of electronic databases, including PubMed, MEDLINE, Cochrane Library, Web of Science (WOS), China National Knowledge Infrastructure (CNKI) and WANFANG Data was performed. Key words used in the literature search were “warfarin”, “Chinese medicine”, “traditional Chinese medicine”, “Chinese patent medicine” etc. and their combinations in a time limit from January 1, 1990 to May 1, 2021. A total of 64 articles were obtained following the selection process, including clinical reports, pharmacological experiments and in vitro experiments which were reviewed to determine the mechanism of the anticoagulant effect of herbal medicine on warfarin. Results: The mechanisms affecting the anticoagulant effect of warfarin are complex, and herbal medicines may enhance and diminish the anticoagulant effect of warfarin through a variety of mechanisms; thus, clinical use needs to be cautious. Some herbal medicines have shown inconsistent results in both in vivo and ex vivo experiments, pharmacology and clinical studies, and should be the focus of future research. Conclusion: With the widespread use of TCM, the combination of warfarin and TCM is more common. This article will promote clinicians’ knowledge and understanding of the TCMs which interact with warfarin, in order to avoid the occurrence of adverse clinical treatment processes, and improve the efficacy and safety.